A case of chronic granulocytopenia associated with vasculitis and amyloidosis. Issue 8 (August 1973) - Jennings, G. H.; Levi, A. J.; Reeve, J.
Abstract : A patient is described with chronic neutropenia who was followed for 22 years. She had varying patterns of neutropenia, sometimes cyclical, sometimes almost agranulocytic; at times the counts were normal. The course was complicated by a vasculitis and finally by large vessel thrombosis; extensive amyloid was found in small vessels at necropsy.